Delaying Iron Therapy until 28 Days after Antimalarial Treatment Is Associated with Greater Iron Incorporation and Equivalent Hematologic Recovery after 56 Days in Children: A Randomized Controlled Trial. Issue 9 (29th June 2016) - Cusick, Sarah E; Opoka, Robert O; Abrams, Steven A; John, Chandy C; Georgieff, Michael K; Mupere, Ezekiel
Abstract: Background: Iron therapy begun concurrently with antimalarial treatment may not be well absorbed because of malaria-induced inflammation. Delaying the start of iron therapy may permit better iron absorption and distribution. Objective: We compared erythrocyte iron incorporation in children who started iron supplementation concurrently with antimalarial treatment or 28 d later. We hypothesized that delayed iron supplementation would be associated with greater incorporation and better hematologic recovery. Methods: We enrolled 100 children aged 6–59 mo with malaria and hemoglobin concentrations of 50.0–99.9 g/L who presented to Mulago Hospital, Kampala, into a randomized trial of iron therapy. All children were administered antimalarial treatment. Children with zinc protoporphyrin (ZPP) ≥80 μmol/mol heme were randomly assigned to start iron supplementation concurrently with the antimalarial treatment [immediate iron (I) group] or 28 d later [delayed iron (D) group]. All children were administered iron-stable isotope 57 Fe on day 0 and 58 Fe on day 28. We compared the percentage of iron incorporation at the start of supplementation (I group at day 0 compared with D group at day 28, aim 1) and hematologic recovery at day 56 (aim 2). Results: The percentage of iron incorporation (mean ± SE) was greater at day 28 in the D group (16.5% ± 1.7%) than at day 0 in the I group (7.9% ± 0.5%; P < 0.001). On day 56, concentrations of hemoglobin and ZPP and plasma ferritin, soluble transferrin receptor (sTfR), hepcidin, and C-reactive protein did not differ between the groups. On day 28, the hemoglobin (mean ± SD) and plasma iron markers (geometric mean; 95% CI) reflected poorer iron status in the D group than in the I group at this intervening time as follows: hemoglobin (105 ± 15.9 compared with 112 ± 12.4 g/L; P = 0.04), ferritin (39.3 μg/L; 23.5, 65.7 μg/L compared with 79.9 μg/L; 58.3, 110 μg/L; P = 0.02), sTfR (8.9 mg/L; 7.4, 10.7 mg/L compared with 6.7 mg/L; 6.1, 7.5 mg/L; P = 0.01), and hepcidin (13.3 ng/mL; 8.3, 21.2 ng/mL compared with 38.8 ng/mL; 28.3, 53.3 ng/mL; P < 0.001). Conclusions: Delaying the start of iron improves incorporation but leads to equivalent hematologic recovery at day 56 in Ugandan children with malaria and anemia. These results do not demonstrate a clear, short-term benefit of delaying iron. This trial was registered at clinicaltrials.gov as NCT01754701.